La estructuración de las relaciones objetales y el papel del superyó en los trastornos de personalidad (2017)
This article is based on the structural description of personality disorders, characterized by a certain level of identity diffusion, in which contradictory aspects of the self, the others and the world are poorly integrated, with predominance of primitive defensive operations, centered on psychic processes with marked defects in cohesion, differentiation and individuation; it shows how the analysis of aspects such as the relational pattern, the identity of the self, narcissism, among other organizing elements of the human psyche, give rise to a particular form in each disorder of the character of structuring and manifesting the instance of the superego.